Social networking sites (SNS) and its influence on job performance at the workplace: the review of the literature - Adzharuddin, Nor Azura; Kander, Sharala Kuti (Human Resource Management Academic Research Society, 2018)
Social networking sites (SNS) connect and link people based on information gathered about them, as saved in their user profiles. Nearly every organization has some connections with a social networking site or two; whether to extend its business or as a means of sharing information and interaction amongst its employees. Although research has found that using social networking sites has also increased the productivity in organizations, there are some organizations that have banned the social networking sites usage in the workplace. This study attempts to look at this issue by examining the previous literature on the usage of social networking sites influencing job performance at the workplace and its influence on job satisfaction, organizational commitment, absenteeism, turnover intention and innovative behaviour. This article reviews the issues on the current situation as regard to the usage of social networking sites.